Defining â€˜difficult dermatophytosisâ€™ beyond chronic/ recurrent forms: A clinico-etiological analysis from a teaching hospital in Northern India: Difficult Dermatophyptosis - Sandhu, Jaspriya; Gupta, Sunil Kumar; Kaur, Navneet; Gupta, Veenu (Journal of Pakistan Association of Dermatologists, 2023)
Background: â€˜Difficult dermatophytosisâ€™ is being increasingly encountered in the last decade in India; encompassing not only chronic/recurrent forms but unusual/atypical presentations posing a diagnostic and therapeutic challenge to the treating physician. Although this has fuelled a lot of research in this space, there is no definition for difficult disease which may not yet be chronic/recurrent such as large/multiple lesions/multifocal or familial clustering. Aim/Objectives: We aimed to study & define â€œdifficult dermatophytosisâ€ encountered frequently; as well as examine demography, patient practices and clinico-etiological pattern among these patients. Patients &Methods: A prospective, cross-sectional study was conducted to include 93(n) cases (after informed consent) from the patients attending the outpatient department in the Department of Dermatology, Venereology & Leprology between August 2019 and August 2020. The inclusion criteria were: - age > 12 years and fulfilling one or more criteria defining â€œdifficult dermatophytosisâ€™ i.e. multiple/large lesions, multifocal, recurrent therapy, multiple relapses, clustering & chronicity. The clinico-demographic data was recorded in a pre-designed pro forma, a KOH examination for skin scraping & fungal culture was done for all cases. Data was analysed with SPSS version 20. Results: Males outnumbered females [M: F =1.2:1] & majority (67.8%) of patients were < 40 years [Mean=34.13 Â±11.5; Median=31yrs]. Body Mass Index (BMI) was higher than 25 in 55.9% cases; mean BMI seen in the study was 25.17Â± 4.60. Multiple /large lesion (90.3%) was most common inclusion criteria followed by multifocal lesions (84.9%). All patients had tinea cruris; tinea corporis was most commonly associated followed by tinea faciei lesions. A significant proportion (76.3%) of cases had Â³4 family members cohabiting with them [Mean= 5.07 Â± 0.03]; more than half (56.98%) had an affected family member [Mean= 0.90 Â± 1.00]. The most common co-morbid condition seen was atopy seen in 16 (17.2%) patients. Presentation for dermatology consult was delayed by > 1 month in 81.7% cases; > 6 months in 47.3% cases & > 1 year in 26.9% cases. A strong statistical association was found of multiple relapses with â€˜delay in dermatology consultsâ€™ (p value=0.002). A significant association of delay was also seen with chronicity (p value=0.046) was also seen. Nearly three-fourth study participants (72%) reported prior use of topical corticosteroid; oral (11.8%) and parental (20.4%) use were also reported. Prior use of luliconazole (40.8%) was most commonly reported among topical drugs, whereas itraconazole was used by 46% patients previously. Irrational use of anti-fungals was seen in 75%; including inappropriate doses (18%), inappropriate duration (34%), poly-pharmacy (6%) and non-compliance (1%). A statistically significant association of irrational use was found with multiple/large lesions (p value=0.008). Conclusions: We propose this definition for the unusual presentations of the disease, particularly in the Indian sub-continent. Better access to clinical dermatology services and rational use of systemic anti-fungals as a means to mitigate difficult dermatophytosis